One-Dimensional Nanostructures - Wang, Zhiming M. (Springer, 2017)
One-dimensional (1D) nanostructures, including nanowires, nanotubes and quantum wires, have been regarded as the most promising building blocks for nanoscale electronic and optoelectronic devices. Worldwide efforts in both the theory and the experimental investigation of growth, characterization and applications of 1D nanostructures have resulted in a mature, multidisciplinary field. In this book, a wealth of state-of-the-art information offers the opportunity to uncover the underlying science from diverse perspectives. Leading researchers elucidate the synthesis and properties of 1D nanostructures for various morphologies and compositions (semiconductor, metal, carbon, etc.) as well as their considerable impact on spintronics, information storage, and the design of field-effect transistors.